The desired directions of the development of marketing strategies adopted by the Ekstraklasa clubs on the basis of a comparative analysis of the revenue structure of the leading Ekstraklasa and Premier League clubs in 2016 and 2017 (using the analysis of annual reports and financial statements as well as the Norton and Kaplan model) - Jedel, J.; Burchard, M. (Baltic Journal of Health and Physical Activity, 2018)
Background: In the article below the authors will try to answer the question about the usefulness on the Polish market of a marketing and management strategy of a sports enterprise, based on the Norton and Kaplan models, based on the examples functioning in the Premier League.